2017
DOI: 10.1080/10428194.2017.1386305
|View full text |Cite
|
Sign up to set email alerts
|

Asparaginase activity levels and monitoring in patients with acute lymphoblastic leukemia

Abstract: Asparaginase is an integral component of multiagent chemotherapy regimens for the treatment of acute lymphoblastic leukemia (ALL). Adequate asparagine depletion is believed to be an important factor in achieving optimal therapeutic outcomes. Measurement of asparaginase activity allows practitioners to evaluate the potential effectiveness of therapy in real time. Asparaginase activity levels can be used to identify patients with silent inactivation and modify therapy in these patients. Patients with silent inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 68 publications
1
68
0
6
Order By: Relevance
“…Because premedication may mask inactivation of asparaginase, therapeutic drug monitoring should be routinely practiced to confirm adequate activity postinfusion. Guidelines have previously been published describing how to properly utilize asparaginase activity levels in children with ALL . Cooper et al showed that in newly diagnosed children with ALL, the use of premedicaton in conjunction with therapeutic drug monitoring reduced the rate of reactions and successfully identified silent inactivation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because premedication may mask inactivation of asparaginase, therapeutic drug monitoring should be routinely practiced to confirm adequate activity postinfusion. Guidelines have previously been published describing how to properly utilize asparaginase activity levels in children with ALL . Cooper et al showed that in newly diagnosed children with ALL, the use of premedicaton in conjunction with therapeutic drug monitoring reduced the rate of reactions and successfully identified silent inactivation .…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines have previously been published describing how to properly utilize asparaginase activity levels in children with ALL. 21,22 Cooper et al showed that in newly diagnosed children with ALL, the use of premedicaton in conjunction with therapeutic drug monitoring reduced the rate of reactions and successfully identified silent inactivation. 23 SAAs were available for most patients one week (6-8 days) after the administration of pegaspargase utilizing a desensitization protocol with a mean of 0.66 ± 0.26 IU/mL (n = 8).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is now available as a CLIA‐certified test with a turnaround time of less than one week, allowing real‐time decision‐making and therapeutic adjustments. Generally accepted SAA assay targets include a minimum trough of ≥ 0.1 IU/mL . However, data indicate that sustained asparagine depletion is critical for improved outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…Generally accepted SAA assay targets include a minimum trough of ≥ 0.1 IU/mL. 25 However, data indicate that sustained asparagine depletion is critical for improved outcomes. 5,26 Furthermore, pharmacokinetic studies indicate that when SAA levels fall below 0.4 IU/mL, asparagine is no longer completely depleted, and begins to rebound, indicating an optimal trough ≥ 0.4 IU/mL.…”
Section: Introductionmentioning
confidence: 99%
“…or i.m. MWF (6 Erwinase doses = 1 PEG‐ASP dose) 15 and the global shortage of Erwinase limits our ability to give higher doses, our data suggest that doses higher than 25 000 IU/m 2 for Erwinase are required to maintain asparaginase activity > 0.1 in over 80% of patients.…”
Section: Discussionmentioning
confidence: 92%